Responsibility and accountability of an engineer in religeous perspective - Olanrewaju, Rashidah Funke; Muyibi, Suleyman Aremu; Sanni, Mistura L. (Sci.Int.(Lahore), 2014)
Accountability is an assessment useful for evaluating an achievement or failure. Meanwhile, professions are based on large knowledge foundations requiring extensive learning, teaching, training, experimenting, preaching and illustrating. Such Skills are pivot to attaining a well-balanced society. Engineering as such is a profession that deals with designing, developing and applying technology into all aspects of human life to improve public welfare. Hence, engineering is one of those fields that play a larger role in contributing to betterment of human welfare. Generally, every profession has its own ethics standard; however, such standards may not necessarily be in line with Islamic belief. As a Muslim Engineer, accountability to our Creator, accountability and responsibility to the society, environments and the non-human nature cannot be separated from the profession. Accountability and responsibility are not mutually exclusive, infact, they occur simultaneously in many instances, for Example,” I TAKE responsibility and I am HELD accountable”. This manuscript presents an assessment of Muslim engineer accountability to his Creator, accountable and responsibility to the society as well as his responsibility to the environment/ non-human nature to give him correct practices of the profession